2000
DOI: 10.1183/09031936.00.16592100
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with nCPAP: incomplete elimination of Sleep Related Breathing Disorder

Abstract: Correct assessment of the overall treatment effectiveness requires knowledge about therapy compliance and efficacy. This study aimed to determine overall long-term apnoea alleviation after continuous positive airway pressure (CPAP) in a complete sleep laboratory cohort.Out of 209 consecutive CPAP candidates (mean age 5712 yrs, body mass index (BMI) 30.05.1 kg . m 2 , respiratory disturbance index (RDI) 32.929 h), follow-up treatment was performed in 149 of them at 9, 18 and 30 months after CPAP prescription. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 32 publications
2
92
0
1
Order By: Relevance
“…Another study, concerning patients with mild-tomoderate OSAS, reported a daily use of 3.1 h corresponding to 44 ¡ 34% of declared sleep time [33]. In a more recent study concerning 74 patients with AHI of 35 ¡ 31 treated with nCPAP for 9 months, a daily compliance of 3.6 ¡ 2.5 h corresponded to 56 ¡ 33% of declared sleep time [34]. These studies were based on the hypothesis of equivalence between nCPAP run time and sleep time.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, concerning patients with mild-tomoderate OSAS, reported a daily use of 3.1 h corresponding to 44 ¡ 34% of declared sleep time [33]. In a more recent study concerning 74 patients with AHI of 35 ¡ 31 treated with nCPAP for 9 months, a daily compliance of 3.6 ¡ 2.5 h corresponded to 56 ¡ 33% of declared sleep time [34]. These studies were based on the hypothesis of equivalence between nCPAP run time and sleep time.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that obstructive sleep apnea was not completely eliminated in all of our patients, and that nasal CPAP might still be more efficacious in reducing the AHI during treatment nights. Nevertheless, reduced compliance with CPAP can significantly compromise long-term therapeutic effectiveness, leaving a significant portion of patients untreated over time (33). Poor CPAP compliance has been attributed to cumbersome masks, and to difficulties in exhaling against a high backpressure (17).…”
Section: Effect Of Tni On Sleep-disordered Breathingmentioning
confidence: 99%
“…Sleep apnoea alleviation SAA compares the therapeutic effect of CPAP and the drug, taking into consideration absolute use of CPAP (adjusted for habitual sleep time) during the 24-week treatment period [3]. The efficacy of CPAP treatment on AHI or ODI in relation to baseline was first calculated.…”
Section: Efficacy Variablesmentioning
confidence: 99%
“…The main consequences of OSA include cardiovascular and metabolic morbidities, and increased daytime somnolence [1,2]. Continuous positive airway pressure (CPAP) constitutes the mainstay of therapy in OSA although long term compliance with the device is incomplete and may be as low as 50% [3]. Therefore, alternative or complementary forms of therapy are actively sought [4,5].…”
Section: Introductionmentioning
confidence: 99%